Efektifitas Aplikasi RDBMS Sebagai Media Arsip Data Pada Kantor Kesehatan Pelabuhan Pekanbaru Berbasis Online - Febriadi, Bayu; Zamsuri, Ahmad (STIKOM Tunas Bangsa Pematangsiantar, 2017)
Kantor Kesehatan Pelabuhan Kelas II Pekanbaru is a government office that concerns about healthy, especially about environment health. There is a problem in case of saving electronic data, also in analyzing daily data both for internal and external data. The office has some computers and other tools that are useful in saving electronic data. In fact, the data are still saved in available cupboards and it is not efficient for an important data that is analyzed for more than one time. In other words, it is not good for a data is needed to be analyzed continuously. Rational Data Base Management System (RDBMS) application is an online based saving data and it uses System Development Life Cycle (SDLC) method. Hopefully, the application will be very useful for employees Kantor Kesehatan Pelabuhan Pekanbaru in managing their work.